Development of the digestive system in early infancy and nutritional management of digestive problems in breastfed and formula-fed infants. Issue 3 (25th January 2022) - Jiang, Hanyun; Gallier, Sophie; Feng, Lifang; Han, Jianzhong; Liu, Weilin
Abstract : Immature gastrointestinal tract and different composition between infant formula and human milk make mild digestive problems more likely to occur in formula-fed infants. Special infant formulas to manage the gastrointestinal problems are reviewed. Abstract : Food digestion and absorption in infants are closely related to early growth and long-term health. Human milk and infant formula are the main food sources for 0–6 month-old infants. Due to the immature gastrointestinal tract of newborns, mild digestive problems, such as inefficient digestion and impaired absorption of proteins, lipids and lactose, and gut dysbiosis, are often seen in infancy. The differences in composition between infant formula and human milk make mild digestive problems more likely to occur in formula-fed infants. In recent years, several types of infant formulas have been developed to treat or reduce gastrointestinal digestive problems in infants. This review summarizes the gastrointestinal environment of infants and the digestion of human milk and different infant formulas. We particularly focus on the common digestive problems and appropriate nutritional solutions that may occur in healthy term infants during the first six months of life.